Purpose and Policy in the Global Community - Russett, B.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2006)
Few topics are as important in the study of international relations as the causes of wealth and poverty, and their interaction with militarization. Few scholars have contributed more to understanding these issues than Bruce Russett. Here Russett shows the linkages between wealth and conflict both substantively and temporally.
Keywords: International relations; Political sociology; International Relations; Political Sociology; Foreign Policy